CHAKANA SAVDO MARKETINGIDA MIJOZGA YOʻNALTIRILGANLIK TAMOYILINI AMALGA OSHIRISH USULLARINI TAKOMILLASHTIRISH (Marketing Journal, 2026)
AbstractThis article examines methods for improving the implementation of the customeroriented principle in retail marketing activities. A comparative analysis of widely usedinternational instruments, including CRM systems, Net Promoter Score methodology,omnichannel integration, personalized marketing, and customer experiencemanagement, is conducted. The current state of Uzbekistanʼs retail market is assessed,taking into account digital infrastructure development and the level of customer-focused technology adoption. Based on the findings, a phased methodological modelfor implementing a customer-oriented approach is proposed. The recommendedframework aims to enhance enterprise competitiveness and strengthen customerloyalty in an increasingly competitive retail environment.Keywords: retail trade, customer orientation, CRM, Net Promoter Score,customer experience, personalization, Uzbekistan.